Risks and benefits of nuclear energy - OECD Nuclear Energy Agency (Nuclear Energy Agency, Organisation for Economic Co-operation and Development, 2013)
In the context of sustainable development policies, decision making in the energy sector should be based on carefully designed trade-offs which take into account, insofar as feasible, all of the alternative options' advantages and drawbacks from the economic, environmental and social viewpoints. This report examines various aspects of nuclear and other energy chains for generating electricity, and provides illustrative examples of quantitative and qualitative indicators for those chains with regard to economic competitiveness, environmental burdens (such as air emissions and solid waste streams) and social aspects (including employment and health impacts). It offers authoritative data and references to published literature on energy chain analysis which can be used in support of decision making.